2001
DOI: 10.1115/1.1415737
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Ultra High Lift Blading in the BR715 LP Turbine

Abstract: The original LP turbine of the BR715 engine featured “High Lift” blading, which achieved a 20-percent reduction in aerofoil numbers compared to blading with conventional levels of lift, reported in Cobley et al. (1997). This paper describes the design and test of a re-bladed LP turbine with new “Ultra High Lift” aerofoils, achieving a further reduction of approximately 11 percent in aerofoil count and significant reductions in turbine weight. The design is based on the successful cascade experiments of Howell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…More engine-specific, high-lift work was presented by Haselbach et al [18] regarding the application of high lift to the BR715 LPT. The authors reported an increase in the measured performance differential between take-off and cruise conditions which was attributed to increased endwall losses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More engine-specific, high-lift work was presented by Haselbach et al [18] regarding the application of high lift to the BR715 LPT. The authors reported an increase in the measured performance differential between take-off and cruise conditions which was attributed to increased endwall losses.…”
Section: Introductionmentioning
confidence: 99%
“…Both the steady and unsteady flow behavior of this blade row have been investigated by several research groups (eg. [18]- [22], [24] [25]). The application of flow control to this airfoil has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In the multistage engine environment, the unsteady wake-induced transition plays a key role in reducing the separation effects up to a level compatible with acceptably low losses. Many studies demonstrate how high-lift [1,2] and ultra-high-lift [3,4] airfoils can be operated with loss control by taking advantage of wake-induced transition in LPT low-Reynolds, number flows. The study of wake-induced transition in LP turbines has thus led to improvements in performance of presentgeneration turbomachinery [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The advent of "Ultra High Lift" blades reported by Haselbach et al. [6] lead to a further reduction in the number of blades of 11%. However, such increases in blade loading were only possible when accompanied by the extensive experimental validation of Brunner et al [7], Howell et al [4] & [8].…”
Section: Introductionmentioning
confidence: 99%